2023
DOI: 10.1002/ana.26590
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of Macrophages and Nucleic Acid Release in Myasthenia Gravis Thymus

Abstract: Objective: Myasthenia gravis (MG) is a neuromuscular disease mediated by antibodies against the acetylcholine receptor (AChR). The thymus plays a primary role in AChR-MG and is characterized by a type I interferon (IFN) signature linked to IFN-β. We investigated if AChR-MG was characterized by an IFN-I signature in the blood, and further investigated the chronic thymic IFN-I signature. Methods: Serum levels of IFN-β and IFN-α subtypes, and mRNA expression for IFN-I subtypes and IFN-stimulated genes in peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In this inflammatory state, thymic epithelial cells have the potential to excessively produce IFN-β, which specifically triggers α-AChR expression, causing self-sensitization and thymic changes that ultimately lead to AChR-MG. The results emphasize the intricacy of the immune system [ 39 ]. In our study, we observed variations in B cells between the high- and low-risk groups of TAMG.…”
Section: Discussionmentioning
confidence: 85%
“…In this inflammatory state, thymic epithelial cells have the potential to excessively produce IFN-β, which specifically triggers α-AChR expression, causing self-sensitization and thymic changes that ultimately lead to AChR-MG. The results emphasize the intricacy of the immune system [ 39 ]. In our study, we observed variations in B cells between the high- and low-risk groups of TAMG.…”
Section: Discussionmentioning
confidence: 85%
“…Non-classical monocytes could be recruited to inflammatory MG thymuses. However, our team recently observed a decrease in the number of thymic macrophages in AChR-MG patients ( 57 ). Non-classical monocytes derived from the linear differentiation of classical monocytes into intermediate monocytes associated with the loss and gain expression of CD14 and CD16, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These observations have led to the hypothesis that ongoing complement attack of myoid and epithelial cells promotes germinal center formation ( 73 ). Some have hypothesized that a deficiency of macrophages leads to impaired removal of necrotic thymomcytes, promoting the proinflammatory environment ( 74 ). This would lead to activation of other self-reactive CD4 + cells by antigen-presenting cells with epitopes derived from the injured tissue, causing further tissue destruction and sensitization of CD4 + cells to an increasingly larger repertoire of tissue epitopes and antigens (“epitope spreading”) ( 75 ).…”
Section: Cellular Pathogenesis Of Mgmentioning
confidence: 99%
“…No evidence suggests other infectious agents to be associated with MG ( 86 ). Release of double-stranded DNA from necrotic macrophages may trigger the inflammatory and subsequent autoimmune reaction in the hyperplastic thymus ( 74 ). Expression profiling of the thymus supports dysregulated apoptotic pathways ( 65 ).…”
Section: Cellular Pathogenesis Of Mgmentioning
confidence: 99%